PENGARUH MODEL PEMBELAJARAN THINK PAIRED SHARE TERHADAP HASIL BELAJAR DAN KEMAMPUAN KOMUNIKASI SISWA SMKN 7 MEDAN - Muhammad Fitri Rahmadana; Isra Rafika (Fakultas Ekonomi Universitas Negeri Medan, 2018)
This study aims to analyze the application of Think Paired Share learning model to learning outcomes and communication skills of students in SMKN 7 Medan. Research that is a Pretest - Posttest Control Group experiment this design uses two classes as a sample, where one class is as an experimental class and another class as a control class. Data of learning outcome variable was taken using test, while data variable of communication skills was taken using questionnaire. While the data analysis techniques used t-test is not paired. The results showed that there were significant differences in learning outcomes and communication skills between experimental and control classes, where the learning outcomes and experimental class communication skills were higher than control classes, whereas previously homogeneity tests were conducted before the tests and questionnaires were given to the respondents. This shows that the Think Paired Share learning model is effective in improving students' learning outcomes and communication skills especially on economic subjects. Keywords: Think Pair Share, Learning Outcomes, Communication Skill, t-test